Promoting Bifunctional Oxygen Catalyst Activity of Double-Perovskite-Type Cubic Nanocrystallites for Aqueous and Quasi-Solid-State Rechargeable Zinc-Air Batteries - Zhong, Yijun; Xu, Xiaomin; Su, Chao; Tadé, Moses; Shao, Zongping (2023)
Transition metal oxide materials are promising oxygen catalysts that are alternatives to expensive and precious metal-containing catalysts. Integration of transition metal oxides with high activity for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is an important pathway for good bifunctionality. In contrast to the conventional physical mixing and hybridization strategies, perovskite-type oxide provides an ideal structure for the integration of the transition metal element atoms on an atomic scale. Herein, B-site ordered double-perovskite-type La1.6Sr0.4MnCoO6 nanocrystallites with ultra-small cubic (20–50 nm) morphology and high specific surface areas (25 m2 g−1) were proposed. Rational designs were integrated to promote the ORR-OER catalysis, e.g., introducing oxygen vacancies via A-site cation substitution, further increasing surface oxygen vacancies via integration of a small amount of Pt/C and nanosizing of the material via a facile molten-salt method. The batteries with the La1.6Sr0.4MnCoO6 nanocrystallites and an aqueous alkaline electrolyte demonstrate decent discharge−charge voltage gaps of 0.75 and 1.10 V at 1 and 30 mA cm−2, respectively, and good cycling stability of 250 h (1500 cycles). A coin-type battery with a gel−polymer electrolyte also presents a good performance.